A study on the suitability of Cassava (Mahilot esculenta) leaf meal as feed for nile tilapia (Oreochromis niloticus) in floating cages. - Vargas, Brummel John D.
Fishmeal is expensive and it is the major protein source in commercially available fish feeds. There are, however, potential fishmeal substitutes like plant leaf meals., A study was conducted to determine primarily the effect of a formulated feed (where fishmeal was partially replaced by cassava leaf meal) on the growth and survival of Nile tilapia fingerlings in floating cages. Nile tilapia fingerlings of mean weight 6.0 g were stocked in cages at a density of 20 pieces/m3. These were fed with the formulated diet and commercial feed ( control ) at the rate of 3 - 5 of biomass for a feeding trial of 78 - days. One-way Analysis of Variance showed that growth and survival of fish fed the two diets did not differ significantly at p<0.05. However, a significantly poor feed conversion ratio (FCR) was obtained in fish fed the cassava leaf meal. Data on growth performance of fish fed the fomulated feed suggests that cassava leaf meal as partial replacement of fish meal is biologically viable as feed for Nile tilapia in net cages. (CORRECTION : m3 )